Polyethylene‐Derived Activated Carbon Materials for Commercially Available Supercapacitor in an Organic Electrolyte System. Issue 10 (10th April 2022) - Yang, Inchan; Mok, Ji Hye; Jung, Meenkyoung; Yoo, Jihoon; Kim, Myung‐Soo; Choi, Dalsu; Jung, Ji Chul
Abstract: High‐performance supercapacitors based on activated carbons (AC) derived from polyethylene (PE), which is one of the most abundant plastic materials worldwide, are fabricated. First, PE carbons (PEC) are prepared via sulfonation, which is a reported solution for successful carbonization of innately non‐carbonizable PE. Then, the physico‐electrical changes of PECs upon a chemical activation process are explored. Interestingly, upon the chemical activation, PECs are converted ACs with a large surface area and high crystallinity at the same time. Subsequently, PE‐derived ACs (PEAC) are exploited as electrode materials for supercapacitors. Resultant supercapacitors based on PEACs exhibit impressive performance. When compared to supercapacitors based on YP50f, representative commercial ACs, devices using PEACs presented considerably good capacitance, low resistance, and great rate capability. Specifically, the retention rate of devices using PEACs is significantly higher than that of YP50f‐based devices. At the high rate of charge−discharge situation reaching 7 A g −1, the capacitance of supercapacitors using PEACs is ≈70% higher than that of YP50f‐based devices. It is assumed that the carbon structure accompanying both large surface area and high conductivity endows a great electrochemical performance at the high current operating conditions. Therefore, it is envisioned that PE may be a viable candidate electrode material for commercially available supercapacitors. Abstract : Polyethylene (PE) is converted into promising activated carbon (AC) for supercapacitor electrodes. The chemical activation leads to PE‐derived ACs (PEAC) with a good graphitization degree as well as a large surface area, and a PEAC (PEC900K) exhibits superior performance to a commercial AC. It is concluded that PE has great potential as a starting material for commercially available supercapacitor electrodes.